The Effect of Promotion and Product Quality on Purchase Decisions - Wijanarko, Denta Ardhian; Solihin, Dede (Indonesian Journal of Entrepreneurship and Startups, 2025)
This study aims to examine the influence of promotion and product quality on purchasing decisions at Carl's Jr. in Central Park, West Jakarta. The method used was an associative quantitative approach, with data collected through questionnaires from 100 respondents. Analysis was conducted using simple and multiple linear regression. The results indicate that promotion and product quality have a positive and significant influence, both partially and simultaneously, on purchasing decisions. Product quality has the greatest influence. These findings imply the importance of promotional strategies and product quality improvements in driving consumer purchasing decisions